The Gold Standard and the Pyrite Principle: Toward a Supplemental Frame of Reference - Brodsky, Stanley L.; Lichtenstein, Bronwen (Frontiers in Psychology, 2020)
In medicine and social sciences, the phrase “gold standard” is often used to characterize an object or procedure described as unequivocally the best in its genre, against which all others should be compared. Examples of this usage are readily available in rigorously peer-reviewed publications, touted by test publishers, and appear in descriptions of methodologies by social science researchers. The phrase does not accurately describe commonly accepted measures, tests, and instruments. Instead, the descriptor can be ambiguous and misleading. This paper presents an overview of the history of the gold standard and its current applications to medicine and the social sciences. We question the use of the phrase “the gold standard” along with suggesting the additional operational use of a “pyrite principle” as a less presumptuous frame of reference. In thinking about validity and standards, the pyrite principle permits an understanding of standards as authoritative rather than fixed constructs in behavioral and health sciences.